Mechanical Characteristics of Grillage Root Foundation for High-Voltage Tower Under Horizontal Conditions - Zehui Ma; Junjie Wang; Xuefeng Huang; Kun Sun; Senlin Yang; Jun Yuan (Buildings)
In response to the issue of reduced horizontal bearing capacity due to inadequate compaction of backfill soil in traditional grillage foundations, a novel grillage root foundation is proposed in this study. That is, the root is introduced into undisturbed soil at a traditional grillage foundation base plate. To assess the applicability of this innovative foundation under horizontal loading conditions, on-site experimental research was conducted. It was employed to comparatively analyze the load–displacement curves, changes in internal forces of steel components, and the development patterns of soil cracks around the foundation between traditional grillage foundations and various sizes of grillage root foundations subjected to horizontal loading. The results indicate that the horizontal bearing capacity of the grillage root foundation increased by 1.3 times compared to traditional grillage foundations, with economic benefits surpassing those of the traditional counterparts. The determination of the “m” value serves as the proportional coefficient of the horizontal resistance coefficient of the foundation soil, and the synthesis of the reactive force provided by the soil to the roots contribute to enhancements in soil resistance and the horizontal bearing capacity of the foundation. The horizontal load at which cracks appear in the grillage root foundation exceeds that of the traditional metal grillage foundation, with a slower rate of development. Finite element analysis was conducted to optimize the arrangement of roots, maximizing the foundation’s bearing capacity. This research provides certain references in terms of enhancing foundation bearing capacity, reducing ground treatment costs, and promoting sustainable development.